2003
DOI: 10.1046/j.1440-1746.2003.03087.x
|View full text |Cite
|
Sign up to set email alerts
|

Balloon‐occluded retrograde transvenous obliteration improves liver function in patients with cirrhosis and portal hypertension

Abstract: From short-term assessment, B-RTO increases hepatic blood flow and improves the metabolic activity of the liver in patients with portal hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
105
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(111 citation statements)
references
References 32 publications
5
105
1
Order By: Relevance
“…Nutritional factors such as insulin and glucagons are favorable for maintaining normal liver function [1,2] . Portal hypertension is important in maintaining hepatopetal blood flow during liver cirrhosis [3][4][5][6] . The present study showed that FPP of the pre-PAD-operation decreased by 0.59 kPa averagely compared to that of post-PAD-operation (P<0.01).…”
Section: Portacaval Shunt For Patients With Portal Hypertension Combimentioning
confidence: 99%
“…Nutritional factors such as insulin and glucagons are favorable for maintaining normal liver function [1,2] . Portal hypertension is important in maintaining hepatopetal blood flow during liver cirrhosis [3][4][5][6] . The present study showed that FPP of the pre-PAD-operation decreased by 0.59 kPa averagely compared to that of post-PAD-operation (P<0.01).…”
Section: Portacaval Shunt For Patients With Portal Hypertension Combimentioning
confidence: 99%
“…B-RTO is also reported to augment portal venous blood flow and improve liver function test findings [214,215]. An elevated hepatic venous pressure gradient after B-RTO is one aspect of the effect of liver function [215].…”
Section: Cq: Is Albumin Infusion Effective For Treatment Of Cirrhoticmentioning
confidence: 98%
“…Comment: Several noncontrolled case series reported that the occlusion of the large portosystemic shunt by B-RTO relieves hepatic encephalopathy [212][213][214][215]. B-RTO is also reported to augment portal venous blood flow and improve liver function test findings [214,215].…”
Section: Cq: Is Albumin Infusion Effective For Treatment Of Cirrhoticmentioning
confidence: 99%
“…The patient would then return for a second and possibly a third session if the gastric varices were not completely obliterated. 9,10,19,22,24 The second strategy was to use an adjunct sclerosant such as 50% glucose solution or absolute alcohol to keep the 5% ethanolamine oleate dose/volume to less than 40 mL. 4,8,17,19 Subsequently, American interventionalists introduced a new sclerosant: 3% Sotradecol, to perform the .…”
Section: Conception and Evolution Of The Brto Proceduresmentioning
confidence: 99%
“…9,10,19,22,24 The second strategy was to use an adjunct sclerosant such as 50% glucose solution or absolute alcohol to keep the 5% ethanolamine oleate dose/volume to less than 40 mL. 4,8,17,19 Subsequently, American interventionalists introduced a new sclerosant: 3% Sotradecol, to perform the . This has caused some Japanese institutions to reconsider use of their ethanolamine oleate concoctions by mixing them with air to create a frothy consistency to the sclerosant with its desired sclerosant dose reduction (relative to volume) and the frothy percolative effect of the sclerosant.…”
Section: Conception and Evolution Of The Brto Proceduresmentioning
confidence: 99%